Teaching Knowledge Test (TKT) dalam Meningkatkan Kompetensi Pedagogik Guru Bahasa Inggris Tingkat SMA Kota Metro dan Dampaknya terhadap Masyarakat Ekonomi Asean (MEA) - Ninsiana, Widhiya (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2018)
This study examines the Teaching Knowledge Test (TKT) to increase the English teacher Pedagogical Competence of senior high school in Metro and Its Impact on the Asean Economic Community (AEC). This purpose of the study are (1) to explain and to describe the Teaching Knowledge Test (TKT) can increase the english teacher pedagogical competence in Metro City; (2) to explain and to describe the Teaching Knowledge Test (TKT) can help the English teacher in developing their competencies in english teaching and learning and its impact on AEC.This study is a qualitative research with analitical approach. The data resources consists of primary and secondary data. The primary data source is the documentation and secondary data is interviews. The techniques data collection in this study are documentation and interview techniques. The data validation is triangulation method by Creswell.The findings of this study are: first, Teaching Knowledge Test (TKT) can increase the teacher pedagogical competence of senior high school in Metro City. It can be seen that the pre-test and post-test TKT result, namely, all participants of TKT get bandmark 3, and it means is good score. Second, Teaching Knowledge Test can provide a positive contribution in increasing the teacher pedagogical competence. This can be proved from the TKT result, that is, just one participant of TKT gets bandmark 4 with a range of score is 60-80 (very good score), and 4 participants get bandmark 3 with a range of score is 41-60 (good score).Based on the findings of the study concluded that Teaching Knowledge Test (TKT) gives a positive contribution to increase the English teacher pedagogical compentence of senior hight school in Metro city, and they are ready to face of AEC with their to cooperate and collaborate the human resources from abroad.